1990
DOI: 10.1143/jjap.29.1139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Impurity Segregation on Crystal Morphology of Y-Bar Synthetic Quartz

Abstract: The effects of Al and H impurities on the crystal morphology of Y-bar synthetic quartz were studied. The growth velocities perpendicular to the Y-axis were evaluated in relation to the Al and H impurity segregations on the growth interfaces. It was found that the -X-growth region has the highest H content and shows the lowest growth velocity, due to the effect of H2O adsorbed on the growth interface in hydrothermal solution. Therefore, the -X-face, (1̄1̄20), always becomes larger in size. Al has a selective ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The main structural differences between these faces are the electrical polarity and the growth velocity. For a right-hand crystal, the growth velocity for +X-is about 2.5 times higher than for -X-face 1,4 . The slowest growth rate of the -X-face is probably connected with the capture of OH species during the hydrothermal growth.…”
Section: Segregation Of Al-and Oh-speciesmentioning
confidence: 87%
See 2 more Smart Citations
“…The main structural differences between these faces are the electrical polarity and the growth velocity. For a right-hand crystal, the growth velocity for +X-is about 2.5 times higher than for -X-face 1,4 . The slowest growth rate of the -X-face is probably connected with the capture of OH species during the hydrothermal growth.…”
Section: Segregation Of Al-and Oh-speciesmentioning
confidence: 87%
“…It is explained by the anisotropy of the growth velocities between the faces formed around the Z-axis. +X-faces growth 2.5 times faster than -X-faces and the growth velocity of mfaces is nearly zero 1,4 . m-faces appearing at the boundary between +X-growth sectors inhibit the progress of the growing layer.…”
Section: Dislocations and Growth Sectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result can be attributed to an increase in the concentration of molecular water defects due to the coalescence of as-grown OH point defects. Previously, it was reported that the incorporation of OH-related defects was responsible for the growth striations appearing in X-ray diffraction topographies of the ÀX-growth sector (Iwasaki, 1980;Iwaski et al, 1990). Thus, the scattering intensities recorded along H 11 2 20 suggest that the linear density of water aggregates is higher along the [11 2 20] direction.…”
Section: Effect Of the Heat Treatmentmentioning
confidence: 95%
“…IBM, where the firstgeneration GF11 project started in 1983 [1,2,3], or TMC [4,5]. In Japan, cooperation of physics and computer science began in 1978 [6] continuing with the QCDPAX series [7]. In 1996, CPPACS, a long term leader of the TOP500 list, was built by CCP scientists together with computer industries [8,9].…”
Section: Introductionmentioning
confidence: 99%